Asymmetric distribution of dynamin-2 and β-catenin relative to tight junction spikes in alveolar epithelial cells. Issue 3 (3rd July 2021) - Lynn, K. Sabrina; Easley, Kristen F.; Martinez, Francisco J.; Reed, Ryan C.; Schlingmann, Barbara; Koval, Michael
ABSTRACT: Tight junctions between lung alveolar epithelial cells maintain an air–liquid barrier necessary for healthy lung function. Previously, we found that rearrangement of tight junctions from a linear, cortical orientation into perpendicular protrusions (tight junction spikes) is associated with a decrease in alveolar barrier function, especially in alcoholic lung syndrome. Using quantitative super-resolution microscopy, we found that spikes in control cells were enriched for claudin-18 as compared with alcohol-exposed cells. Moreover, using an in situ method to measure barrier function, tight junction spikes were not associated with localized increases in permeability. This suggests that tight junction spikes have a regulatory role as opposed to causing a physical weakening of the epithelial barrier. We found that tight junction spikes form at cell–cell junctions oriented away from pools of β-catenin associated with actin filaments, suggesting that adherens junctions determine the directionality of tight junction spikes. Dynamin-2 was associated with junctional claudin-18 and ZO-1, but showed little localization with β-catenin and tight junction spikes. Treatment with Dynasore decreased the number of tight junction spikes/cell, increased tight junction spike length, and stimulated actin to redistribute to cortical tight junctions. By contrast, Dynole 34–2 and MiTMAB altered β-catenin localization, and reduced tight junction spike length. These data suggest a novel role for dynamin-2 in tight junction spike formation by reorienting junction-associated actin. Moreover, the greater spatial separation of adherens and tight junctions in squamous alveolar epithelial cells as compared with columnar epithelial cells facilitates analysis of molecular regulation of the apical junctional complex.